Analisis Pendapatan Petani Karet di Dusun Sei Jera Desa Sungai Landai Kecamatan Mestong - Buhari, Ismail; Halim, Abd (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to determine how the characteristics of rubber farmers in Sei Jerat Sub-Village and analyze how the income of rubber farmers in Sei Jerat Sub-Village. The type of data collected is questionnaire data and direct interviews to the field. The population in this study was the community in Sei Jerat Hamlet with a total of 544 people. Determination of the sample is done using Random Sampling as many as 80 respondents who have a rubber plantation farming business. The results of the research from 80 people the number of respondents the average farm income per person is Rp 24,141,120 / year with total fixed and non-fixed costs of Rp 5,475,181 / person / year then the total income per person is Rp 18,683,939 / year and the average income per person is Rp 1,557,078 / month rubber farming income in the research location is lower than the minimum wage of Jambi Province.